ANALISIS SIFAT MEKANIK DAN TERMAL PADA REAKTOR BIODIESEL DENGAN MENGGUNAKAN METODE FINITE ELEMENT ANALYSIS (FEA) - Fikri, Ahmad; Muarif, Agam; Razi, Ar; Syahrani, Irma; Ashari, Muhammad Rayhan (BUANA SAINS, 2025)
This study aims to analyze and evaluate the Structural and Thermal Performance of a Biodiesel Reactor using Finite Element Analysis (FEA) simulation. The reactor was designed using Autodesk Fusion 360 and simulated under various static pressure conditions (10, 40, 100, 150, and 170 bar) and thermal loads (27, 100, 500, 1000, and 1600Â°C) using three stainless steel materials: AISI 202, AISI 304, and 316L. The results indicate that the maximum allowable operational pressure for SS 316L and AISI 405 is 40 bar, with corresponding deformations of 68Ã—10â»Â³ mm, 62Ã—10â»Â³ mm, and 64Ã—10â»Â³ mm respectively. Stress and deformation values showed a direct correlation with applied pressure. Thermal analysis revealed thermal gradients ranging from 2Ã—10â»Â³ to 100Ã—10â»Â³ (Â°C)/mm and heat flux values between 2.72Ã—10â»âµ and 200Ã—10â»âµ W/mm across all materials. The study demonstrates that increasing external temperature directly enhances both thermal gradient and heat flux distribution throughout the reactor structure..